Infant HIV diagnostics : supply chain in Sub-Saharan Africa - Deo, Sarang; Ben Har, Avidan; Shields, Bill; Naware, Mihir ([London] : SAGE, 2016)
In this case, Roger Osayende, a former management consultant, must advise the Ministry of Health of Ektu, a fictional country in Central Africa, on how to implement a new point-of-care diagnostic test for infants with HIV.
Originally Published in: Deo, S., Ben Har, A., Shields, B., & Naware, M. (2012). Infant HIV Diagnostics: Supply Chain in Sub-Saharan Africa (case revised 20/02/2012). 5-410-753. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Business logistics -- Case studies; Health facilities -- Materials management -- Africa, Sub-Saharan -- Case studies; HIV infections -- Diagnosis -- Africa, Sub-Saharan -- Case studies